2022
DOI: 10.1111/ped.15164
|View full text |Cite
|
Sign up to set email alerts
|

Precordial Doppler to assess vascular access in children: A preliminary report

Abstract: Background Delayed identification and dysfunction of peripheral intravenous (PIV) infiltration can lead to serious injury in children. This preliminary study aimed to describe the application of precordial Doppler ultrasound to detect and confirm the correct PIV access in children with congenital heart disease (CHD). Methods This study was conducted on children (<18 years) diagnosed with CHD and admitted to the pediatric intensive care unit (PICU) of a single center after cardiac surgery or cardiac catheteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Second, the Doppler sound may be attributed to the turbulence ejected from the left ventricle into the aorta rather than that from the right ventricle into the pulmonary artery. Our previous study demonstrated that the Doppler sound was audible even in patients with bidirectional Glenn or Fontan shunts who had a direct connection between the superior vena cava and pulmonary artery 5,10 . In these cases, the administered NS did not enter the right cardiac chamber; however, microbubbles would enter from the pulmonary arteries into the left cardiac chambers because of the presence of right to left intracardiac or intrapulmonary shunts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the Doppler sound may be attributed to the turbulence ejected from the left ventricle into the aorta rather than that from the right ventricle into the pulmonary artery. Our previous study demonstrated that the Doppler sound was audible even in patients with bidirectional Glenn or Fontan shunts who had a direct connection between the superior vena cava and pulmonary artery 5,10 . In these cases, the administered NS did not enter the right cardiac chamber; however, microbubbles would enter from the pulmonary arteries into the left cardiac chambers because of the presence of right to left intracardiac or intrapulmonary shunts.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that the Doppler sound was audible even in patients with bidirectional Glenn or Fontan shunts who had a direct connection between the superior vena cava and pulmonary artery. 5,10 In these cases, the administered NS did not enter the right cardiac chamber; however, microbubbles would enter from the pulmonary arteries into the left cardiac chambers because of the presence of right to left intracardiac or intrapulmonary shunts. In these patients, the insonating Doppler beam could be changed by the turbulence in the left ventricle due to the injected NS, resulting in changes in the pitch of the heartbeat.…”
Section: Discussionmentioning
confidence: 99%
“…The monitor detects the Doppler signals derived from the patient’s intracardiac blood flow. A small amount of normal saline (NS) is then administered via a PIV line to induce changes in the Doppler signals 5 , 6 . The precordial Doppler can be attached during the induction of anesthesia and potentially be used throughout the surgery.…”
Section: Introductionmentioning
confidence: 99%
“…We previously used an NS injection dose of 0.5 mL/kg, based on findings obtained from a small, exploratory data set 5 , 6 . Therefore, the minimally required dose of NS for confirming correct PIV placement remains unknown.…”
Section: Introductionmentioning
confidence: 99%